Distúrbios osteomusculares e grau de incapacidade funcional em policiais militares - Trindade, Ana Paula Nassif Tondato da (2013)
The military police represent a class of differentiated workers, with particular characteristics, due to the coexistence with the violence and activities developed during the performance of the work functions, which can cause musculoskeletal problems. Thus, the aim of the present study was to assess the prevalence of musculoskeletal disorders and the degree of physical incapacity of the military police, as subsidies for health promotion intervention programs. The study was a cross-sectional descriptive study with a stratified and representative sample of the population of military police in the region of Araçatuba / SP. The officers responded to the Nordic questionnaire and the Oswestry Disability Index (OID). Of the 262 military police officers assessed, 216 (82.4%) were male, with an average age of 37 ± 7.2 years. It was observed that 198 (75%) of the policemen had pain in the last 12 months and 135 (51.5%) in the last seven days, with the lumbar region being the most affected (25.2%). Regarding the results for the OID questionnaire, the majority of respondents (64.9%) had minimal disability. The results of the present study showed a high prevalence of musculoskeletal symptoms, especially in the last 12 months and with involvement of the lumbar region, showing this to be a chronic problem. These findings suggest the importance of periodic evaluations and the need to implement health promotion strategies to improve working conditions, minimizing the prevalence of musculoskeletal disorders.